Length-weight relationship and condition factor of Hydrocynus forskahlii (Cuvier, 1819) in River Yobe, Northeast, Nigeria - Ashley-Dejo S. Segun; Ogah S. Ijabo; Babdu Yusuf (Aceh Journal of Animal Science, 2022)
This study examined the length-weight relationship and condition factor of Hydrocynus forskahlii (Cuvier, 1819) in River Yobe, Northeast, Nigeria. A total of 350 fish species were collected from commercial fishermen at four landing sites (Gogaram, Dogona, Bize, Azbak) within the study area between June to November 2020. The morphometric and meristic characteristics examined could be attributed   to environmental variations (water temperature, stress, food availability, spawning ground, fishing intensity and sex). Monthly mean condition factor (1.19 ± 1.03) shows significant difference (P 0.05) during the sampling duration while highest mean condition factor was recorded in October (1.38 ± 1.15). Also change in weight of the sampled fish was caused by 77.4% change in length. A linear relationship was established with b value (1.2656) indicating a negative allometric growth pattern while correlation coefficient (r2 = 0.7775) indicated that LWR model is reliable. This study bridged literature gap on LWR and condition factor of Hydrocynus forskahlii in River Yobe, hence further research should be encouraged on the water body for sustainable utilization, decision making and policy formulation.